Multilevel Signal Analyzer Tool for Optical Communication System - M.F.L Abdullah; Rahmat Talib (International Journal of Electrical and Computer Engineering (IJECE), 2012)
This paper presents an educational software interface tool to analyze multilevel signal at the receiver of an optical communication system. This tool provides visualization in terms of eye-diagram and bit/symbol error rate along the symbol duration using Gaussian approximation method. Besides that, maximum Q-factors, minimum BER and corresponding threshold level are also displayed. This tool is developed using Matlab as an interface programming tool. The developed analyzer has been used to analyze 2, 4 and 8-PAM signal for an optical communication system. A commercial software known as OptiSystem™ has been used to develop and simulate the multilevel optical system. The performance of the develop analyzer has been validated with the build in analyzer of OptiSystem.DOI:http://dx.doi.org/10.11591/ijece.v2i4.1464